Development of Communicative Competence Among Psychology Students - Kulchytska, Anna; Mudryk, Alla; Fedotova, Tetiana (East European Journal of Psycholinguistics, 2015)
The article empirically determines components (competences) of communicative competence of students-psychologists: capability to conduct and accept attention signs; to support other person, sympathize her; adequately react on fair and unfair criticism, provocative behavior towards themselves; be capable of accepting support from the others; opportunity to apply to companion with request, but can reply by refusal on strange request, say “no” in negative situation; have skills of efficient interaction with other people. Surely, communicative competence of future psychologist depends on his demand in communication, width, initiative. Not less important factors of communicative competence of specialist are such factors as communication clearness, ease and stability of communication. The longitude study  showed that during studying students-psychologists’ level of communicative competence increased. There also increased indices of authoritative, aggressive and friendly type of interpersonal relations. During studying students become more self-confident, independent in opinions and beliefs, straight and insistent in aim achievement. They formed skills of being good advisers and organizers. Until the third year of study they are different by high capability to interwork and making friendly relations with surrounding.ReferencesYemelyanov, Yu. (1991). Obuchenie paritetnomu dialogu [Teaching EqualDialogue]. Leningrad: Leningrad State University.Fetiskin, N. (2002). Socialno-Psyhologicheskaya Diagnostika Razvitiya Lichnosti iMalykh Grupp [Social and Psychological Diagnostic of Individual and Small GroupDevelopment]. Moscow: Psyhoterapiya.